IDENTIFIKASI KEMAMPUAN BERPIKIR KREATIF SISWA PADA PENYELESAIAN MASALAH GEOMETRI - Novita Sari; Agung Prasetyo; Beti Rita Mayasari; Puji Nugraheni (Universitas Batanghari Jambi, 2026)
This study aims to measure the creative thinking ability of eighth-grade students in geometry material at Muhammadiyah Sempor Middle School. This type of research is descriptive qualitative. The technique for selecting subjects uses a purposive method with two selected subjects. The data collection techniques employed are observation, tests , interviews, and field notes methods. The steps in data analysis include data reduction, data presentation, and drawing conclusions/verification. Based on the findings of the research conducted on eighth-grade students at Muhammadiyah Sempor Middle School, it was concluded that the creative thinking ability demonstrated by students in solving geometry problems is still at a fairly creative level. This is because students are limited in answering questions in two ways ; they have not been patient in compiling answers in detail (writing knowns , asked questions, steps/stages, and final conclusions), leading them to focus immediately on working on mathematical models. Furthermore, students have not been able to solve problems in their own unique and unconventional ways, so they continue to use the methods provided by the teacher. Students also encounter obstacles, such as being inconsistent in writing units and mathematical symbols in the form of roots. Additionally, students demonstrate inaccuracy in writing the names of the angles of the triangle